GREEN CONSUMERISM IN INDIAN MARKET (International Journal of Food and Nutritional Sciences, 2022)
Global awareness of environmental sustainability and the necessity of responsible consumption practices has grown in recent years. The idea of "green consumerism" has drawn a lot of attention as consumers think more and more about how their purchases will affect the environment. For the study, 260 young people from Pune City were chosen as a representative sample. People who were actively making consumption decisions and had the ability to adopt green consumerism were included in the sample. They ranged in age from 18 to 30. The survey's findings show that respondents' attitudes towards environmental concerns and green consumption are usually favourableWith mean scores above 4 on a 5-point scale for all awareness and understanding-related items, the one-sample data show that the sample population has a high level of knowledge and understanding of environmental issues. The sample population is also interested in learning more about environmental sustainability and conservation, and they feel obligated to protect the environment. These results imply that the sample population has a high feeling of personal responsibility for preserving the environment and is actively engaged in learning about environmental concerns in order to make informed judgements.The correlation analysis also shows a moderately positive association between green consumption and environmental consciousness. This implies that people who are more environmentally conscious are more likely to practise green purchasing.